Estimating the bioaccumulation of lead and cadmium in the Soil and Eucalyptus gomphocephala and Ficus nitida Trees on the roadsides of Derna City - Masoud Mostafa Zatout; Salma Ismail Jibril (African Journal of Advanced Pure and Applied Sciences, 2024)
The aim of this study was to assess the bioaccumulation of heavy elements (lead and cadmium) in soil and leaves of Ficus nitida and Eucalyptus gomphocephala trees in three different areas in Derna city, and to explore their potential use in biomonitoring air pollution with heavy elements in urban areas. The first area represented the city center, the second area was near the cement factory in Fataeh, and the third area was at the steam station. The experiment was conducted using a completely randomized design with three factors. Results indicated significant differences in lead content among the study areas, while no significant differences were observed in cadmium content. The cement factory area recorded the highest lead content. Regarding tree species, significant differences were found in lead content between Ficus nitida and Eucalyptus gomphocephala trees, while no significant differences were observed in cadmium content. Concerning sample type, no significant differences were found between leaves and soil in cadmium and lead content. The results also showed that the interaction between study areas and tree species was not significant for lead and cadmium content, while the interaction between tree species and sample type was significant for lead content but not for cadmium content. Additionally, the interaction between study areas, tree species, and sample location was not significant for cadmium content, but it was significant for lead content.